The industrial ephemeral : labor and love in Indian architecture and construction - Dharia, Namita Vijay, 1980- (Atelier (Oakland, Calif.), 2022)
"What transformative effects does a multimillion-dollar industry have on those who work within it? The Industrial Ephemeral presents the untold stories of the people, politics, and production chains behind architecture, real estate, and construction in areas surrounding New Delhi, India. The personal histories of those in India's large laboring classes are brought to life as Namita Vijay Dharia discusses the aggressive environmental and ecological transformation of the region in the twenty-first century. Urban planning and architecture are messy processes that intertwine migratory pathways, corruption politics, labor struggle, ecological transformations, and technological development. The aggressive actions of the construction activity produce an atmosphere of ephemerality in urban regions, creating an aesthetic condition that supports industrial political economy. Dharia's brilliant analysis of the aesthetics and experiences of work lends visibility to the struggle of workers in an era of growing urban inequality"--